Experimental Investigation on the Effectiveness of Solar Still and Its Effect on Adsorption with Various Dyes. (18th July 2022) - Sakthivel, T. G.; Arjunan, T. V.; Natrayan, L.; Kumar, P. V. Arul; Patil, Pravin P.; Manikandan, R.; Muniappan, A.; Paramasivam, Prabhu
Abstract : The typical solar still with internal and exterior heat transfer was used to test the impact of mixing various colours into the basin water. This is well-known that enhancing distillation involves adding black dye to basin water. Identical design parameters create two single-slope basin-type solar stills (effective area 0.5 m 2 ). This study conducted experiments to add black, green, blue, and red dyes to basin water during the winter for 24 hours. For more than a month, the amount of distilled water recovered per hour, with varying temperatures and solar activity (May 2021). This research aims to (i) examine the effect of various dyes with basin water on the internal and external heat transfer and performance of the system and (ii) study the effect of adding dyes into the basin water on increasing energy balance by the solar system. This is indicated by the fact that the introduction of colours into the basin water has a major impact on external and interior heat transfer. The evaporation, radiation, and heat transfer rate from liquid to glass significantly impact how well the filtration system works.